A Comparative Study of Public Open Space Handling Methodology in Urban Area - B W Sulistyo; Antariksa Antariksa; Surjono Surjono; L Hakim (Institut Teknologi Sepuluh Nopember, 2018)
Public open spaces (POS) handling in urban areas, regardless of their form, can be approached by various methods based on the potential and problems that exist in the POS. The public open spaces here can be in the form of green open spaces in the area, roads, parks, or outside natural spaces that function as public service facilities, including areas of the site developed into POS. Through this article we will look at four different cases for POS in three European cities and one Indonesian city which are carried out with different approaches as presented from the four scientific articles studied. The selected cities are located in Turkey, Cyprus, Montenegro and Denpasar, Indonesia. The reason for choosing four cities in various countries was also based on the physical and cultural character of these countries. By studying the different approaches taken, it is hoped that an understanding of the relationship between POS management results and the POS factual problems will result in the conclusion of the most appropriate approach to choose. Thus, it is expected to also find a relationship between the physical and cultural character of a country with the pattern of handling the city's public space.